Hotspot de violência na região metropolitana de Belém-PA: análise da distribuição espacial dos homicídios no período de janeiro de 2017 a setembro de 2018 - COSTA, Caio Leonardo Fonseca da (2019)
This work presents the spatialisation of violent deaths in the Metropolitan Region of Belém from January 2017 to September 2018. The objective was to identify the hotspot of violence, as well as the times and periods of greatest occurrence of homicides in the referred area, relating such occurrences to the socioeconomic conditions of the member municipalities of the RMB. The methodology consisted in geocoding the occurrences of homicides registered by the Deputy Secretary of Criminal Analysis SIAC / SEGUP, which did not have geographic coordinates. The work will be made available to assist in the creation of public safety policies and also to social policies aimed at the most needy population and almost always the main victim of urban violence. The geocoding method has proved to be adequate for spatial analysis of crimes and, therefore, the use of geotechnology could help in the implementation of a public security policy that is beyond the direct use of the armed police, but involves at the same time, the creation and development of educational, cultural, sporting, leisure and public health actions for the population of the most vulnerable areas, where alarming homicide rates occur in the Metropolitan Region of Belém.